أثر إضافة مياه عصر الزيتون (الجفت) في بعض الخصائص الفيزيائية للتربة - النائب, حسام; الإبراهيم, أنور; مصري, زهير (Latakia University Journal -Biological Sciences Series, 2019)
أجري البحث في محطة بحوث كتيان التابعة لمركز بحوث إدلب في الفترة 2007-2010، حيث أضيفت مياه عصر الزيتون إلى التربة سنوياً بمعدلين 10، 20 لتراً/م2 في بداية شهر تشرين أول، أما معاملة الشاهد فبقيت دون إضافة. أخذت عينات من التربة في بداية التجربة لتوصيف التربة كيميائياً وفيزيائياً قبل إضافة مياه عصر الزيتون، كما تم إجراء التحاليل الفيزيائية لعينات التربة في نهاية التجربة (التوصيل المائي، السعة الحقلية، نقطة الذبول، الماء المتاح، الغربلة الجافة والرطبة واختبار هشاشة حبيبات التربة). تمت زراعة التربة بمحصول القمح الطري. دلت النتائج على أن هذه الإضافات المقننة لم تؤثر سلباً في خصائص التربة الفيزيائية، بل ساعدت في زيادة قيم التوصيل المائي والنسبة المئوية للسعة الحقلية والماء المتاح، وفي تحسن بناء التربة وتكوين تجمعات ترابية أكثر ثباتية. The research was carried out at the Ktian research station, Edlib research center, during 2007-2010. Olive mill wastewater (OMWW) added into the soil annually first of October with tow rates 10, 20 L/m2, the control treatment remained without application. Soil samples were taken before adding OWW for soil characterization (chemically& physically) also physical analysis have been performed at the end the experiment (water conductivity, field capacity, available water, wilting point, dry and wet sieving and test of the soil particles brittleness). The soil is cultivated with soft wheat. The results indicated that Olive wastewater considered addition did not affect negatively on the physical soil properties, but helped to increase the values of water conductivity, the percentage of field capacity and available water, and to improve of soil structure and performing soil aggregates more stability.